2017
DOI: 10.1186/s12906-017-2044-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pharmacodynamic effects of Pycnogenol® in patients with severe osteoarthritis: a randomized controlled pilot study

Abstract: BackgroundThe standardized maritime pine bark extract (Pycnogenol®) has previously shown symptom alleviating effects in patients suffering from moderate forms of knee osteoarthritis (OA). The cellular mechanisms for this positive impact are so far unknown. The purpose of the present randomized pilot controlled study was to span the knowledge gap between the reported clinical effects of Pycnogenol® and its in vivo mechanism of action in OA patients.MethodsThirty three patients with severe OA scheduled for a kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Jessberger et al . found that Pycnogenol can reduce the expression of MMP3 , MMP13 , and the pro‐inflammatory cytokine IL1β, so it has some effect on severe bone and joint inflammation. In our study, MMP3 was found to be overexpressed in osteoarthritis synovial cells.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Jessberger et al . found that Pycnogenol can reduce the expression of MMP3 , MMP13 , and the pro‐inflammatory cytokine IL1β, so it has some effect on severe bone and joint inflammation. In our study, MMP3 was found to be overexpressed in osteoarthritis synovial cells.…”
Section: Discussionsupporting
confidence: 49%
“…Wang et al found that MMP3 expression was significantly increased after transfection of HS6ST2-specific interfering RNA (siRNA) into C28/12 cells, indicating that HS6ST2 may be involved in the pathogenesis of osteoarthritis and Kashin-Beck disease by affecting aggrecan metabolism 23 . Jessberger et al found that Pycnogenol can reduce the expression of MMP3, MMP13, and the pro-inflammatory cytokine IL1β, so it has some effect on severe bone and joint inflammation 24 . In our study, MMP3 was found to be overexpressed in osteoarthritis synovial cells.…”
Section: Matrix Metalloproteinase-3 Plays An Important Role In Bone-rmentioning
confidence: 99%
“…Constituents and metabolites of Pycnogenol were able to inhibit the activity of inflammatory mediators within the joint. 60,61 Three double-blind, placebo-controlled studies in 293 patients demonstrated a better physical function, less joint stiffness, and less pain. A mean improvement of 40% of these symptoms was observed in all studies.…”
Section: Mobilitymentioning
confidence: 99%
“…Its affinity to accumulate in macrophages, monocytes, and endothelial cells were demonstrated [42]. Investigation conducted in patients with severe OA showed that expression of matrix metalloproteinases (MMP-3 and MMP-13) and IL-1β in chondrocytes was decreased after intake of Pycnogenol ® , as well as level of ADAMTS-5 in serum [43]. Plasma obtained from volunteers taking Pycnogenol ® orally for 5 days decreased activation of transcription factor NF-κB in macrophages and inhibited COX-1 and COX-2 [44,45].…”
Section: Herbal Medicinal Products For Oral Use In the Treatment Of Omentioning
confidence: 99%